Pengaruh Bauran Pemasaran dan Citra Merek Terhadap Keputusan Pembelian Konsumen Restaurant Pempek Beringin Radial Palembang - Putri Vareri Angelieta; Roswaty Roswaty; Mohammad Kurniawan (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The study aims to analyze the influence of mixed marketing and brand image on consumer purchasing decisions Restaurant Pempek Beringin Radial Palembang. This research was conducted at the Restaurant Pempek Beringin Radial Palembang. The data analysis technique used is double linear regression analysis. The sample used is 107 respondents at the Restaurant Pempek Beringin Radial Palembang, using quantitative research methods. The data collection is done with the dissemination of a questionnaire. Based on the results of research stated marketing mix has a positive and significant impact on consumer purchasing decisions Restaurant Pempek Beringin Radial Palembang. The brand image also gives a positive and significant influence on consumer purchasing decisions Restaurant Pempek Beringin Radial Palembang. Then it can be concluded that the results of the research stated the mix of marketing and brand image have a significant and positive impact on the consumer purchase decisions.